PENGARUH IKLAN, PERSONAL SELLING, DAN WOM TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA NMAX DI KABUPATEN NGANJUK - Vijaya, Rahul; Meilina, Restin; Bhirawa, Sigit Wisnu Setya; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2025)
The objectives of this study was to analyze the effects of advertising, personal selling, and word of mouth (WOM) on purchasing decisions of Yamaha Nmax motorcycles in Nganjuk Regency, partially and simultaneously. This study employs a quantitative approach using a causal research design. The population of this study consists of consumers who have purchased and use the Yamaha Nmax 155. The sample comprises 40 respondents. Data analysis was conducted using multiple linear regression analysis with SPSS for Windows. The results of the study indicate that: (1) advertising has a significant partial (individual) effect on purchasing decisions; (2) personal selling has a significant partial (individual) effect on purchasing decisions; (3) word of mouth (WOM) has a significant partial (individual) effect on purchasing decisions; and (4) advertising, personal selling, and word of mouth (WOM) simultaneously (collectively) have a significant effect on purchasing decisions.